The Sandpile Model: Optimal Stress and Hormesis - Martha Stark (SAGE Publishing, 2012)
The sandpile model (developed by chaos theorists) is an elegant visual metaphor for the cumulative impact of environmental stressors on complex adaptive systems - an impact that is paradoxical by virtue of the fact that the grains of sand being steadily added to the gradually evolving sandpile are the occasion for both its disruption and its repair. As a result, complex adaptive systems are continuously refashioning themselves at ever-higher levels of complexity and integration - not just in spite of "stressful" input from the outside but by way of it. Stressful input is therefore inherently neither bad ("poison") nor good ("medication"). Rather, it will be how well the system (be it sandpile or living system) is able to process, integrate, and adapt to the stressful input that will make of it either a growth-disrupting (sandpile-destabilizing) event or a growth-promoting (sandpile-restabilizing) opportunity. Too much stress - "traumatic stress" - will be too overwhelming for the system to manage, triggering instead devastating breakdown. Too little stress will provide too little impetus for transformation and growth, serving instead simply to reinforce the system's status quo. But just the right amount of stress - "optimal stress" - will provoke recovery by activating the system's innate capacity to heal itself.